A Qualitative Research Experience of the Strategic Role of Users and Customers on the Architectural Offices Innovativeness - Nilüfer AKINCITÜRK; Yasemin ERBİL (Megaron, 2010)
There are many actors influencing innovation during building design and construction periods. One of these is the architect. The architect plays a major role in various phases of the construction process, and as such, is an important player in the construction sector. In addition, architectural offices function as a co-ordinating hub for the activities of various professions involved in the construction process. For these reasons, architects assume an important role in construction networks. Competition is becoming more and more related with innovation. Accordingly, there is growing interest in the role of clients within the construction industry similiar with other sectors. Because of this, many factors such as company size, business strategy, customer relations, sales and marketing approaches and innovative networks are becoming more and more vital to survive in the construction sector. A case study was carried out to better understand the role of clients and the factors influencing the innovation process within architectural design offices. As the goal of this research was to understand and interpret the whole process of innovation, a qualitative research method was selected. A purposive method has been used in order to ensure that those who are considered a source of important information become a part of the research. Data was collected from the analyses unit via face to face interviews. In this paper the research process is explained and the collected data evaluated.